Sensory ecology of the frog-eating bat, Trachops cirrhosus, from DNA metabarcoding and behavior. (21st October 2020) - Jones, Patricia L; Divoll, Timothy J; Dixon, M May; Aparicio, Dineilys; Cohen, Gregg; Mueller, Ulrich G; Ryan, Michael J; Page, Rachel A
Abstract: Metabarcoding of prey DNA from fecal samples can be used to design behavioral experiments to study the foraging behavior and sensory ecology of predators. The frog-eating bat, Trachops cirrhosus, eavesdrops on the mating calls of its anuran prey. We captured wild T. cirrhosus and identified prey remains in the bats' fecal samples using DNA metabarcoding of two gene regions (CO1 and 16S). Bats were preying on frogs previously unknown in their diet, such as species in the genus Pristimantis, which occurred in 29% of T. cirrhosus samples. Twenty-three percent of samples also contained DNA of Anolis lizards. We additionally report apparently rare predation events on hummingbirds and heterospecific bats. We used results from metabarcoding to design acoustic and 3D model stimuli to present to bats in behavioral experiments. We show predatory responses by T. cirrhosus to the calls of the frog Pristimantis taeniatus and to the rustling sounds of anoles moving through leaf-litter, as well as attacks on a stuffed hummingbird and a plastic anole model. The combination of species-specific dietary information from metabarcoding analyses with behavioral responses to prey cues provides a unique window into the foraging ecology of predators that are difficult to observe in the wild. Abstract : We designed behavioral experiments that exposed wild-caught tropical frog-eating bats to acoustic and 3D model stimuli from the prey species we had determined wild bats were eating using DNA sequencing of prey remains in fecal samples. This combination of techniques allowed us to show that bats are consuming previously unknown frog species and that bats are eating some unusual prey such as hummingbirds.